2021
DOI: 10.1021/acs.analchem.1c00528
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tim4 Grafting Strongly Hydrophilic Metal–Organic Frameworks Immunoaffinity Flake for High-Efficiency Capture and Separation of Exosomes

Abstract: Exosomes have become the most ideal analysis target for liquid biopsy since they carry a large amount of genetic materials. The study on exosomes has great significance for cancer diagnosis and prognosis. However, the extremely low concentration renders the development of a robust exosomes enrichment technique, with the merits of low nonspecific cell adhesion, high-capture efficiency, and easy nondestructive release of captured exosomes, of vital significance. We successfully designed and developed a novel Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…In short, ILI and Fe 3 O 4 were prepared according to previous reports. 53,54 For the preparation of Fe 3 O 4 @ILI-01, 0.30 g of Fe 3 O 4 was dispersed into 10 mL of methanol (MeOH) containing 0.81 g of Zn(NO 3 ) 2 Á6H 2 O (27.2 mmol). The suspension solution was stirred at 70 1C for 1 h, and then 1.01 g of ILI (3.13 mmol) was introduced for the generation of ILI-01 on the surface of Fe 3 O 4 .…”
Section: Methodsmentioning
confidence: 99%
“…In short, ILI and Fe 3 O 4 were prepared according to previous reports. 53,54 For the preparation of Fe 3 O 4 @ILI-01, 0.30 g of Fe 3 O 4 was dispersed into 10 mL of methanol (MeOH) containing 0.81 g of Zn(NO 3 ) 2 Á6H 2 O (27.2 mmol). The suspension solution was stirred at 70 1C for 1 h, and then 1.01 g of ILI (3.13 mmol) was introduced for the generation of ILI-01 on the surface of Fe 3 O 4 .…”
Section: Methodsmentioning
confidence: 99%
“…In this detection principle, nanomaterials not only act as matric materials for exosomes capture, but also can amplify MS signal due to the large amount of elements in nanomaterials. [222][223][224][225][226][227] Recently, Zhang et al reported an ultrasensitive inductively coupled plasma−mass spectrometry (ICP-MS) method for the detection of exosomes by using UCNPs as element labels. 228 As shown in Figure 18, three different elements (Y, Eu, and Tb) doped UCNPs modified with three different aptamers were linked to AuNPs, forming three statellite-like nanoassemblies.…”
Section: Other Methodsmentioning
confidence: 99%
“…Magnetic beads immobilized with Tim4 can capture exosomes quickly, and intact exosomes can be easily eluted by chelating agent ( Xu et al, 2018 ). Zhang et al developed a novel Tim4@ILI-01 immunoaffinity flake material for the enrichment of exosomes from serum ( Figure 2A ; Zhang et al, 2021b ). The gene analysis of eluted exosomes showed that the level of the expressed CD44 gene was significantly high in lung adenocarcinoma patients.…”
Section: Isolation and Enrichment Strategies Of Exosomesmentioning
confidence: 99%
“… (A) Schematic diagram of the membrane modified by fusion peptide-mediated exosomes. Reprinted with permission from Zhang et al, 2021b . (B) Protein ligating enzymes mediate a covalent conjugation of exosomes with peptides.…”
Section: Peptide Recognition-guided New Strategies For Exosome Researchmentioning
confidence: 99%